Isu morfofonologi bahasa Melayu: menangani kepelbagaian varian dalam korpus (Jurnal Bahasa, 2005)
This paper examines the aspect of Malay morphophonology, specifically the irregular morphemic alternations that surface in the morphological derivation of complex words in the language. The alternaLion is attested with a number of variants that semantically denotes equivalent lexical meaning. For instance, a passive word diketengahkan will be realized in three different active forms, namely mengketengah-kan, tnengetengahkan, and mengenengahkan. Based on the DBP cor-pus, all the three variants are widely used by the Malay speakers. Previous studies seem to accept only one variant as the norm or the standard form, while the others are regarded illformed and ungrammatical. Such analysis is very prescriptive and does not tie in with the modern linguistics approach. Linguistics is a descriptive discipline, and an adequate theory should be able to account for all the variants, principally if the alternations are phonologically motivated and in agreement with the grammar of the language. This paper attempts to account for all the attested alternations by adopting the theoretical framework of autosegmental phonology. The study proves that the existing variants are well-formed because they are derived by the basic and general phonological rules that constitute part of Malay gram-mar.